Matched wavelets for differential protection of power transformers using differential evolution - Roy A.; Singh D.; Misra R.K. (My University, 2025)
The differential protection of transformer by the use of matched wavelet method is proposed in this work. The basic concept behind the method is finding wavelet matching in shape to the inrush or fault waveform independently. Then using inrush wavelet and fault wavelet to detect and discriminate inrush and fault in differential current waveform. Getting best approximate matched inrush or fault wavelet by the use of differential evolution algorithm is the novelty of approach. This approach provides fast discriminating ability (in nearly half cycle). © 2019, Institute of Advanced Scientific Research, Inc. All rights reserved.